Flexible and Stretchable Electronics - Zhigang Wu (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Flexible and stretchable electronics are receiving tremendous attention as future electronics due to their flexibility and light weight, especially as applications in wearable electronics. Flexible electronics are usually fabricated on heat sensitive flexible substrates such as plastic, fabric or even paper, while stretchable electronics are usually fabricated from an elastomeric substrate to survive large deformation in their practical application. Therefore, successful fabrication of flexible electronics needs low temperature processable novel materials and a particular processing development because traditional materials and processes are not compatible with flexible/stretchable electronics. Huge technical challenges and opportunities surround these dramatic changes from the perspective of new material design and processing, new fabrication techniques, large deformation mechanics, new application development and so on. Here, we invited talented researchers to join us in this new vital field that holds the potential to reshape our future life, by contributing their words of wisdom from their particular perspective.